Commentary: Productivity implications for generative AI role-based prompts as a networked hermeneutic - Rintel, Sean (Discourse & Communication, 2024)
Commentary for Membership categorisation, sociological description and role prompt engineering with ChatGPT - William Housley, Patrik Dahl, 2024 As Housley and Dahl (2024) demonstrate, role-based prompts for Generative AI (GenAI) systems are based on vernacular resources of membership categorization and action description, representing a networked hermeneutic of lay and professional sociology. As a Microsoft Human-Computer Interaction researcher, I see three implications for designing GenAI systems for productivity.